Impact of Prenatal Exposure to Opioids, Cocaine, and Cannabis on Eye Disorders in Children. Issue 6 (December 2020) - Auger, Nathalie; Rhéaume, Marc-André; Low, Nancy; Lee, Ga Eun; Ayoub, Aimina; Luu, Thuy Mai
Abstract : Objectives: Prenatal substance exposure is associated with abnormal visual evoked potentials in offspring, but whether ocular abnormalities are present past infancy is unclear. We determined the association between prenatal substance exposure and hospitalizations for eye disorders in childhood. Methods: We conducted a longitudinal cohort study of 794, 099 infants born between 2006 and 2016 in all hospital centers in Quebec, Canada. We identified infants prenatally exposed to opioids, cocaine, cannabis, and other illicit substances and followed them over time to assess eye disorders that required in-hospital treatment, including retinal detachment and breaks, strabismus, and other ocular pathologies. We calculated incidence rates and hazard ratios (HR) with 95% confidence intervals (CI) for the association of prenatal substance exposure with risk of eye disorders, adjusted for patient characteristics. Results: Infants exposed to substances prenatally had a higher incidence of hospitalizations for eye disorders compared with unexposed infants (47.0 vs 32.0 per 10, 000 person-years). Prenatal substance exposure was associated with 1.23 times the risk of hospital admission for any eye disorder during childhood compared with no exposure (95% CI 1.04–1.45). Risks were greatest for strabismus (HR 1.55, 95% CI 1.16–2.07) and binocular movement disorders (HR 1.96, 95% CI 1.00–3.83). Opioid use was strongly associated with the risk of ocular muscle disorders (HR 3.15, 95% CI 1.98–5.01). Conclusions: Prenatal substance exposure is significantly associated with future hospitalizations for eye disorders in childhood. Efforts to minimize substance use in women of reproductive age are needed in light of the current opioid epidemic. Abstract : Supplemental Digital Content is available in the text